Joint venture as a risk management tool: experience from construction sector. (9th August 2019) - Morkunas, Mangirdas; Volkov, Artiom; Rudiene, Elze; Skvarciany, Viktorija
This study aims at examining the possibility of using a joint venture as a risk management tool for companies engaged in the construction business. Based on completely different risk map of a stand-alone and joint venture companies and using the analytical hierarchy process model method for evaluating the importance of particular risk factors for both cases we found, that depending on a company's ability to deal with different types of business risks, joint venture can be used as a risk management tool in particular situations. The results deviation from classical risk management literature has been found, that can be attributed to new theory applicable to small open economies in Central and Eastern Europe.